Seasonal variation in microplastics and zooplankton abundances and characteristics: The ecological vulnerability of an oceanic island system. (August 2022) - Sambolino, Annalisa; Herrera, Inma; Álvarez, Soledad; Rosa, Alexandra; Alves, Filipe; Canning-Clode, João; Cordeiro, Nereida; Dinis, Ana; Kaufmann, Manfred
Abstract: The ingestion of microplastics (MPs - plastic particles <5 mm) by planktivorous organisms represents a significant threat to marine food webs. To investigate how seasonality might affect plastic intake in oceanic islands' ecosystems, relative abundances and composition of MPs and mesozooplankton samples collected off Madeira Island (NE Atlantic) between February 2019 and January 2020 were analysed. MPs were found in all samples, with fibres accounting for 89 % of the particles. MPs and zooplankton mean abundance was 0.262 items/m 3 and 18.137 individuals/m 3, respectively. Their monthly variations follow the seasonal fluctuation of environmental parameters, such as currents, chlorophyll- a concentration, sea surface temperature and precipitation intensity. A higher MPs/zooplankton ratio was recorded in the warm season (May-Oct), reaching 0.068 items/individual when considering large-sized particles (1000–5000 μm). This is the first study to assess the seasonal variability of MPs in an oceanic island system providing essential information respecting its ecological impact in pelagic environments. Graphical abstract: Unlabelled Image Highlights: Abundance and composition of microplastics and zooplankton were analysed monthly. Oceanographic processes and precipitation significantly affect these traits. Fibres were the most abundant microplastic type found. The microplastics/zooplankton ratio is greater in the warm season. Seasonal variability might influence microplastics' ecological hazard.